A MODEL OF CONFLICT MANAGEMENT STRATEGY IN BUSINESS ORGANIZATION - Nadezda Todorova; Denislava Doneva; Angel Stoyanov (Journal of Bio-Based Marketing, 2024)
The purpose of the article is to analyze the existing principles of strategic conflict management and propose an algorithm for modeling an effective conflict management strategy in a business organization. The main methods used in developing the strategy model are scientific abstraction, the method of analysis, and synthesis. Scientific abstraction is a process by which a scientific researcher summarizes and presents the main ideas, results, and conclusions of his research. Conflicts must be recognized and resolved quickly and effectively before they affect the long-term functioning and success of the business organization. It goes without saying that the negative effects of the emergence of conflicts, as well as their management, through inappropriate approaches, methods, and strategies should not be underestimated. If this happens, management efficiency may suffer in the long term, which may lead to the liquidation of the business organization in the form in which it was originally organized. The stated principles, approaches, and strategies are reliable tools for effective conflict management in the business organization.